Repercussões da equoterapia nas relações socioafetivas da criança com atraso de desenvolvimento por prematuridade - Queiroz, Juliana Fonsêca de (2004)
This research has as objective to study families of children that have a delay on neuropsicomotor development due to prematurity and that are frequenting an interdisciplinary therapy called equine therapy, a therapeutical approach that has as primordial source the horse and its environment. It was carried through with two children of the Caxangá Golf & Country Club Nucleus of Equine therapy, its respective families and professionals who accompany the children in the therapeutical process. The instruments used consisted of comments of the children in the sessions; interviews with therapists of the institution, with the parents and, when necessary, with other carers. The importance of the bond of the child with the animal was evidenced by its bigger participation in the therapy and by the family investment, as this intervenes positively to the course of the therapy; the importance of the interaction between the child, the team and other practitioners in the socialization process; the adequacy of the stimulations of the equine therapy environment by the interdisciplinary team, as well as the exchanges between them and the family; the knowledge of the child s family history for understanding its behavior and family events; the importance of the child s feedback as to its development in the family to remain investing and believing. An improvement of the child in the socio-affective aspect was perceived, facilitating and being facilitated by the family relations. Therefore, through the research we understood the repercussions of the equine therapy, as well as its intervening elements in the socioaffective development of the child with neuropsicomotor retardation due to prematurity